The effect of density turbulent diffusion intensity on magnetohydrodynamic wave processes in a spherical layer of electrically conducting liquid - Peregudin, S; Peregudina, E; Kholodova, S (Journal of physics. Conference series, 2019)
The paper considers large-scale 3D wave motion of weakly compressible and perfectly conducting inhomogeneous inviscid liquid subject to a magnetic field and the Coriolis force, with due account the spherical topography of bounding surfaces. The results of the studies can be used in geophysics and astrophysics, and in particular, in the study of dynamical processes occurring in the Earth liquid core and in stellar interiors. Moreover, they can be also employed in evaluation of magnetohydrodynamic characteristics of a liquid medium and for estimation of the parameters of the wave disturbance in the electromagnetic field induced by the corresponding hydrodynamic excitement. In addition, the above results can be used in the study of magnetohydrodynamic processes in engineering devices and in the study of foreground energy materials.